The foundations and criteria of university self-evaluation and quality assurance: Algerian students' perspectives (University of Setif 1 as a model) - Khalissa, Medjili; Ghedjati, Ahlam (The International tax journal, 2025)
As human investment constitutes the fundamental pillar for any modification, change, or reform in the university education system, investing in the development of the university student—as a key input to this system—is therefore a primary objective for any reform. Given that the student is a fundamental partner in the educational process and plays a significant role in ensuring and enhancing the quality of their university (Al-Hadi, 2021), the significance of the current study emerges. This study aimed to measure the quality of university facilities and equipment and the availability of a healthy environment from the perspective of students at the University of Setif. To achieve the study's objectives, a questionnaire was administered to a sample of 100 students from the University of Setif 1. The questionnaire consisted of two parts: the first part included items related to the students' general information, while the second part comprised six axes. The first axis pertained to pedagogical facilities, the second to the availability of pedagogical tools, the third to cleanliness, the fourth to safety and security, the fifth to health, and the sixth to accommodation and housing. Each axis contained five questions.